Impact of the pre-collection phase at different intensities of source segregation of bio-waste: An Italian case study. (July 2016) - Di Maria, Francesco; Micale, Caterina; Morettini, Emanuela
Highlights: Pre-collection emission contribution due to bio-waste were investigated for an existing urban area. Pre-collection emissions affected up to 40% GWP. For collection frequency of 7 day −1 pre-collection emission resulted comparable to those of fuel consumption of vehicles. Optimal collection frequency for bio-waste was 2 day −1 . Abstract: The contribution of the N2 O and CH4 emissions generated during pre-collection of the organic fraction of municipal solid waste was investigated for an existing Italian collection district in a life cycle perspective. This district consisted of about 24, 000 inhabitants generating 35.6 Mg/day of municipal solid waste, of which 7.27 Mg/day was the organic fraction. Different source segregation intensities and collection frequencies (day −1 ) were analyzed. The amount of the organic fraction not segregated at source was assumed to be collected commingled with the residual waste. The main findings showed that the lower was the collection frequency, the lower was the fuel consumption of the collection vehicles. For a source segregation intensity of 0%, the amount of fuel consumed ranged from 3.92 L to 1.73 L for each Mg of organic fraction as the collection frequency was decreased from 1 day −1 to 14 day −1, respectively. The maximum fuel consumption for the collection of 1 Mg of organic fraction for a source segregation intensity of 50% was from 8.6 L/Mg to 2.07 L/Mg for a collection frequency of 1 day −1 and 14 day −1, respectively. On the other hand the lower was the collection frequency, the higher was the amount of greenhouse gas generated during the pre-collection phase. The life cycle analysis showed that these emissions could affect the global warming potential of the scenarios analyzed up to 40%, exceeding the reduction of the emissions due to lower fuel consumption. In any case, as already reported by other authors, the uncertainty analysis confirmed the higher value for the uncertainty associated to the emissions from biological processes compared to those generated by industrial and combustion ones.